POTENSI miRNA SEBAGAI ALAT DIAGNOSTIK POLIP KOLON: SEBUAH TINJAUAN PUSTAKA - Jusni, Louis Fabio Jonathan; Adiwardhana, Jason; Kadharmestan, Maxmillion Budiman (Essential: Essence of Scientific Medical Journal; Vol 19 No 2 (2021): Volume 19 No. 2 (Juli - Desember 2021) Essential: Essence of Scientific Medical Journal, 2022)
Introduction : Colonic polyps are distinct tissue growth inside the lumen of the colon and an expected  precursor for the development of colorectal cancer. Prospective diagnostic modalities such as miRNA might be ideal to evaluate the progression. There are evidence from multiple studies that implied certain dysregulation of miRNA indicates pathologic changes regarding colonic polyps Aim: This review aims to provide overview of the diagnostic capabilities of miRNA in colon polyp and identify gaps of knowledge for further studies Method : A review based on Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) was conducted with the database from Pubmed, Science Direct, and Proquest Result : A total of five studies has reported diagnostic accuracies of miRNA in distinguishing adenoma polyp and normal, adenoma polyp and hyperplastic polyp, sessile serrated adenoma/polyps and hyperplastic polyp, colon polyp and colorectal cancer. Conclusion: miRNAs could be a potential biomarker for colon polyp. Further diagnostics studies, in particular those with clinical values, need to be conducted.